2000
DOI: 10.1016/s0885-3924(99)00158-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opioids on Driving Ability

Abstract: Driving has been regarded as an activity of daily living that is important in maintaining a person's independence in the community, access to employment, and social activities. Many patients, however, using opioid medications on a regular basis (Chronic Opioid Analgesic Therapy: COAT) to ameliorate their intractable pain have been restricted from driving out of concern that skills would be impaired and driving safety compromised by these medications. Yet there are no driving studies which have explored the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 35 publications
7
85
0
9
Order By: Relevance
“…A study of cancer patients taking stable, long term opioid therapy compared with a group taking no opioids demonstrated no significant difference in functions related to driving ability (32). This observation has been duplicated in subsequent studies (33)(34)(35)(36)(37)(38). Cognitive deficits in opioid-treated patients are more often due to the concurrent use of sedative medications such as benzodiazepines.…”
Section: Side Effectsmentioning
confidence: 90%
“…A study of cancer patients taking stable, long term opioid therapy compared with a group taking no opioids demonstrated no significant difference in functions related to driving ability (32). This observation has been duplicated in subsequent studies (33)(34)(35)(36)(37)(38). Cognitive deficits in opioid-treated patients are more often due to the concurrent use of sedative medications such as benzodiazepines.…”
Section: Side Effectsmentioning
confidence: 90%
“…Findings regarding opioids are less consistent; experimental studies show moderate effects on driving with no clear doseresponse relationship (Strand et al, 2016), whereas a review of epidemiological studies showed statistically significant associations between opioids and road traffic crashes in 17 of 25 studies (Gjerde et al, 2015). The greatest risks from this drug class may be among opioid-naive patients rather than those on long-term therapy (Dassanayake et al, 2011;Fishbain et al, 2003;Galski et al, 2000;Leung, 2011;Wilhelmi & Cohen, 2012), suggesting that drug tolerance plays an important role in determining opioid-related driving risks.…”
Section: Riving Under the Influence Of Drugs (Duid)mentioning
confidence: 99%
“…Desses, dois foram ensaios randomizados, do tipo crossover e duplo-cego 8,9 , dois foram ensaios clínicos controlados 10,11 , três foram ensaios clínicos não-controlados [12][13][14] , dois foram relatos de caso 15,16 , dois estudos foram classificados como ensaios que usaram voluntários saudáveis para a formação do grupo de comparação 17,18 . Os desenhos dos estudos de melhor qualidade 8,9 , controlados e randomizados, mostraram que pacientes com dor crônica não-oncológica em uso de opióide não apresentam alteração da função cognitiva.…”
Section: Resultados Efeitos Dos Opióides Na Função Cognitiva De Doentunclassified
“…Os desenhos dos estudos de melhor qualidade 8,9 , controlados e randomizados, mostraram que pacientes com dor crônica não-oncológica em uso de opióide não apresentam alteração da função cognitiva. A maioria dos estudos de menor qualidade, não-randomizados, também não referiu alteração da função cognitiva [10][11][12][13][14][15][16][17] , sendo que alguns mostraram melhora de algumas funções, como a atenção/concentração e velocidade psicomotora 10,[12][13][14][15] . Somente um estudo que utilizou voluntários no grupo de comparação concluiu pela piora na atenção e memória dos pacientes tratados com opióides 18 Além da variabilidade dos estudos quanto ao desenho, observouse grande variabilidade quanto ao número de sujeitos estudados, tipo e dose de opióides, e testes utilizados para avaliação cognitiva.…”
Section: Resultados Efeitos Dos Opióides Na Função Cognitiva De Doentunclassified